Governance : a very short introduction / Mark Bevir. - Bevir, Mark (Very short introductions., 2012)
Generally referring to all forms of social coordination and patterns of rule, the term 'governance' is used in many different contexts. In this 'Very Short Introduction', Mark Bevir explores the main theories of governance and considers their impact on ideas of governance in the corporate, public, and global arenas.